Biographic notes from a collection of indumentary - Oliveira, Madson Luis Gomes de (2021)
The Sophia Jobim Clothing Collection – CSJ, from the National Historical Museum – MHN, belonged to Maria Sophia Jobim Magno de Carvalho (1904-1968), who was a teacher, costume designer, journalist, researcher and collector of costumes, accessories and stories. After Sophia’s death, her entire collection was donated to the National Historical Museum – MHN. CSJ is divided into three parts: historical archive; library and technical reserve. The research studies the entire collection, but it is still in progress, so we present the partial results that, inevitably, are confused with the collector’s biography. Our approach is similar to investigations similar to those dealing with collections of clothing / fashion with a focus on the cultural biography of objects, as follows: Amy de la Haye, Lou Taylor and Eleanor Thompson (2005); Igor Kopytoff (2008); Rita Andrade (2008). This kind of perspective helps us to understand the collection that Sophia Jobim gathered, throughout her professional career, culminating in the inauguration of MIH. So it is necessary to ask: Where did these pieces come from? How were they acquired? Who were its former owners? Is it possible to verify and answer these questions? When acquiring art objects and clothing pieces/ accessories for her growing collection, Sophia seemed to structure “her museum”, as we see in this text. Thus, the cultural objects she bought went through the process of commodification and valuation, which, therefore, would reflect these values in the trajectory of her collector, and vice versa.